Structure retrieval in liquid-phase electron scattering. Issue 2 (23rd December 2020) - Yang, Jie; Nunes, J. Pedro F.; Ledbetter, Kathryn; Biasin, Elisa; Centurion, Martin; Chen, Zhijiang; Cordones, Amy A.; Crissman, Christopher; Deponte, Daniel P.; Glenzer, Siegfried H.; Lin, Ming-Fu; Mo, Mianzhen; et al.
Abstract : A novel analysis method for the direct retrieval of the real-space distribution of charged particle pairs from liquid-phase electron scattering. Abstract : Electron scattering on liquid samples has been enabled recently by the development of ultrathin liquid sheet technologies. The data treatment of liquid-phase electron scattering has been mostly reliant on methodologies developed for gas electron diffraction, in which theoretical inputs and empirical fittings are often needed to account for the atomic form factor and remove the inelastic scattering background. In this work, we present an alternative data treatment method that is able to retrieve the radial distribution of all the charged particle pairs without the need of either theoretical inputs or empirical fittings. The merits of this new method are illustrated through the retrieval of real-space molecular structure from experimental electron scattering patterns of liquid water, carbon tetrachloride, chloroform, and dichloromethane.